2007
DOI: 10.1111/j.1365-2648.2007.04308.x
|View full text |Cite
|
Sign up to set email alerts
|

STAMP: components of observable behaviour that indicate potential for patient violence in emergency departments

Abstract: Staring and eye contact, Tone and volume of voice, Anxiety, Mumbling and Pacing provides a useful, practical nursing violence assessment framework to assist nurses to quickly identify patients, families and friends who have a potential for violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 20 publications
3
105
0
1
Order By: Relevance
“…Patients wait a long time in the ED and are under stress regarding their underlying medical condition. These factors, concomitantly with substance abuse and psychiatric comorbidities, also contribute to violence toward staff (3,9,51). Emergency departments appear to be especially problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Patients wait a long time in the ED and are under stress regarding their underlying medical condition. These factors, concomitantly with substance abuse and psychiatric comorbidities, also contribute to violence toward staff (3,9,51). Emergency departments appear to be especially problematic.…”
Section: Discussionmentioning
confidence: 99%
“…In fact environmental factors are hugely important determinants of behaviour in inpatient settings (Daffern, 2007). Research carried out in accident and emergency departments has shown that pacing and staring were two of the top five observable behaviours reported by staff (Luck et al, 2007) as relevant to aggressive behaviours. Results from the present study support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Early recognition of the warning signs of patient violence may reduce the incidence of occurrence or increase preparedness for such an event. Luck, Jackson and Usher (2007) and more currently Wilkes et al (2010) identified five and 17 behavioral cues, respectively; however there is not a substantial amount of literature testing the usefulness of either of these tools. Kim, Ideker, and Todicheeney-Mannes (2012) discussed the psychometric properties of violence assessment tools and identified the need for such tools to determine overall usefulness as demonstrated by a satisfactory sensitivity, specificity, and inter-rater reliability.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…This research provided the benchmark for testing a simple screening tool for violence. The 17-item checklist, the Aggressive Behavior Risk Assessment Tool (ABRAT), was derived from the published M55 tool, the 5-item STAMP (Luck et al, 2007) and an investigator-developed item. A prospective cohort study was conducted at an acute care hospital in which primary nurses completed a 17-item checklist upon admission.…”
Section: Violence Against Nurses In Emergency Department (Ed)mentioning
confidence: 99%
See 1 more Smart Citation